2020
DOI: 10.3389/fmicb.2020.608506
|View full text |Cite
|
Sign up to set email alerts
|

Delivering Beneficial Microorganisms for Corals: Rotifers as Carriers of Probiotic Bacteria

Abstract: The use of Beneficial Microorganisms for Corals (BMCs) to increase the resistance of corals to environmental stress has proven to be effective in laboratory trials. Because direct inoculation of BMCs in larger tanks or in the field can be challenging, a delivery mechanism is needed for efficient transmission of the BMC consortium. Packaged delivery mechanisms have been successfully used to transmit probiotics to other organisms, including humans, lobsters, and fish. Here, we tested a method for utilizing rotif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…[10][11][12][13][14] . Despite the challenges of applying microbes to surfaces beneath the saltwater ocean, coral microbiomes have been manipulated ex situ through the introduction of probiotic strains by incubation, topical application 11,13,14,119,120 or direct feeding 121 . Microbiome transplantation using resistant donor corals from the wild has also demonstrated thermal protective effects on coral populations 10 , such as increased growth 120 and reduced stress responses under heat (including mortality evasion following thermal stress bleaching) 11,13,119 , oil exposure 12,14 and pathogen challenges 11,116 , all of which are accompanied by microbiome restructuring.…”
Section: Coralsmentioning
confidence: 99%
“…[10][11][12][13][14] . Despite the challenges of applying microbes to surfaces beneath the saltwater ocean, coral microbiomes have been manipulated ex situ through the introduction of probiotic strains by incubation, topical application 11,13,14,119,120 or direct feeding 121 . Microbiome transplantation using resistant donor corals from the wild has also demonstrated thermal protective effects on coral populations 10 , such as increased growth 120 and reduced stress responses under heat (including mortality evasion following thermal stress bleaching) 11,13,119 , oil exposure 12,14 and pathogen challenges 11,116 , all of which are accompanied by microbiome restructuring.…”
Section: Coralsmentioning
confidence: 99%
“…This has been shown to be feasible in cnidarian model systems such as Hydra, Nematostella, and Aiptasia (Murillo-Rincon et al, 2017;Domin et al, 2018;Medrano et al, 2019;Costa et al, 2021;Dungan et al, 2021), but is only beginning to be explored in reefbuilding corals and other cnidarians (Lin et al, 2019;Cunning and Baker, 2020;Weiland-Bräuer et al, 2020). Experiments that apply a combination of antibiotics treatments followed by targeted probiotic delivery or "microbiome recovery" treatments will yield insights into whether disturbed coral-associated bacteria communities and host stress response phenotypes can be "rescued" by the re-introduction of one or several beneficial microbes (Peixoto et al, 2017(Peixoto et al, , 2021Rosado et al, 2018;Damjanovic et al, 2019;Assis et al, 2020;Santoro et al, 2021). Future work would also benefit from the inclusion of baseline samples and additional time points to track the temporal changes in bacteria community composition and transcriptome responses across coral colonies.…”
Section: Implications For Coral Conservation and Disease Intervention...mentioning
confidence: 99%
“…Although there was evidence for increased relative abundance of some consortium members in the host microbiome, the key limitation of the present study was the inability of the bacteria to persist after inoculation. Bacteria delivery via bioencapsulation in A. salina is used in aquaculture to ensure dosed bacteria are ingested (Hai et al 2010 ), and a method for corals using rotifers has been reported (Assis et al 2020 ). Researchers using probiotics to treat stony coral tissue loss disease (SCTLD) in the field have also tested strategies such as weighted enclosures, paste applied directly to SCTLD lesions, and slow release beads to improve bacteria‐coral contact and maintain probiotic concentrations in the open marine environment (Smithsonian Marine Station 2020 ).…”
Section: Discussionmentioning
confidence: 99%